Longevity of pulmonary rehabilitation benefit for chronic obstructive pulmonary disease—health care utilisation in the subsequent 2 years. Issue 1 (24th November 2019) - Walsh, James R; Pegg, Jane; Yerkovich, Stephanie T; Morris, Norman; McKeough, Zoe J; Comans, Tracy; Paratz, Jenny D; Chambers, Daniel C
Abstract : Background: The primary aim was to determine the healthcare utilisation benefits including respiratory-related hospital admissions, hospital admission days and emergency department presentations in the 0–12 and 12–24 months postpulmonary rehabilitation compared with the 12 months preprogramme. Methods: An observational, data-linkage design of 11 standardised pulmonary rehabilitation programmes were used. All programmes were 8 weeks in duration with two supervised exercise sessions per week and were required to use the national pulmonary rehabilitation recommendations with regard to programme organisation, exercise training guidelines and multidisciplinary education. For each participant with chronic obstructive pulmonary disease (COPD), healthcare utilisation data were collected for the 12 months preprogramme and 24 months postprogramme. Results: 426 participants (231 males, FEV1 49.3 (19.6) % predicted) were studied. The number of respiratory admissions/participant/year decreased from 0.7 (1.1) in the 12 months preprogramme to 0.5 (1.9) in the 12 months postprogramme, p=0.083; but increased in the 12–24 months postprogramme to 1.0 (2.3), p<0.001. The hospital days/participant/year improved from 4.0 (7.8) days in the 12 months preprogramme to 2.5 (8.5) days in the 12 months postprogramme, p<0.001; but increased in the 12–24 months postprogramme to 6.1 (16.6) days, p=0.004. The emergency department presentations/participant/year improved from 1.15 (1.75) in the 12 months preprogramme to 0.9 (1.8) in the 12 months postprogramme, p=0.003; but increased in the 12–24 months postprogramme to 2.0 (3.3), p<0.001. Conclusion: Pulmonary rehabilitation significantly improves hospital days and emergency department presentations in the first 12 months postprogramme. Healthcare utilisation benefits in the second 12 months are less clear.